An improved method for grinding mill filling measurement and the estimation of load volume and mass. (1st January 2021) - Hilden, Marko M.; Powell, Malcolm S.; Yahyaei, Mohsen
Graphical abstract: Highlights: A method is presented for measuring mill filling safely from the trunnion. New equations of load volume including in the conical ends and occupied by lifters. Calculate load mass from mill crash-stop and grind-out filling measurements. Spreadsheet calculator and procedure pdf supplied as supplementary material. Abstract: The fraction of mill volume occupied by rocks, grinding media and slurry in grinding mills are dominant factors influencing AG and SAG mill power draw and grinding rate. Hence accurate mill filling measurements are needed for modelling mills. To that end, it is usually necessary to enter the confined space of a grinding mill, a task that involves a degree of safety risk and a potentially lengthy plant stoppage. This paper discusses a range of available methods for measuring and calculating mill filling and introduces a new technique for accurately measuring filling that eliminates the need to enter the mill in most cases. The new method offers engineers and researchers a safer and faster method for quantifying the filling level in industrial SAG and ball mills, and allows the surface profile to be surveyed, without requiring the contents to be level. The paper also details formulas for calculating the filling level and load volume, which unlike previously published equations, also consider the volume in the conical ends and the volume occupied by the mill shell lifters.